The Nordic Labor Market and Migration - Ho, Giang; Shirono, Kazuko (Washington, D.C. : International Monetary Fund, 2015)
The large influx of migrants to Nordic countries in recent years is challenging the adoptability of Nordic labor market institutions while also adding to potential growth. This paper examines the trends, economic drivers, and labor market implications of migration to Nordic countries with a particular focus on economic migration as distinct from the recent large flows of asylum seekers. Our analysis finds that migration inflows to the Nordics are influenced by both cyclical and structural factors. Although migration helpfully dampens overheating pressures during periods of strong demand, and over the longer term will cushion the decline in labor supply from population aging, in the near-term unemployment can rise, especially among the young and lower-skilled. The analysis highlights the need to adapt Nordic labor market institutions in a manner that better facilitates the integration of migrants into employment. In particular, greater wage flexibility at the firm level and continued strong active labor market measures will help improve labor market outcomes among immigrants.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet